The Effect of Sustainability Performance, Institutional Ownership, Profitability and Capital Structure on Company Value - Nuzulul Nasoihul Ibad; Ulfi Kartika Oktaviana (Yayasan Riset dan Pengembangan Intelektual, 2023)
Jakarta Islamic Index (JII) is a sharia stock index that has a fairly high level of market capitalization in the Indonesian capital market. However, over the last five years, the JII market capitalization index has continued to fluctuate, due to changes in share prices of companies that are members of it. Therefore, it is necessary to study indicators that can influence the share price of JII companies. This research purpose to see the influence of sustainability performance, institutional ownership, profitability and capital structure on JII company value in 2018-2022. The method used in this research is quantitative causality and the data used is in the form of sustainability report and company annual reports or secondary data . This research randomly selected samples using certain criteria, so that 7 companies were selected as samples. this research produces : (1) sustainability performance, institutional ownership and profitability have no impact on company value (2) capital structure has a significant impact on company value.